Oxygen Vacancy Introduction to Increase the Capacity and Voltage Retention in Li‐Excess Cathode Materials. Issue 1 (23rd November 2022) - Huang, Jianping; Zhong, Peichen; Ha, Yang; Lun, Zhengyan; Tian, Yaosen; Balasubramanian, Mahalingam; Yang, Wanli; Ceder, Gerbrand
Abstract : Li‐rich rocksalt oxides are promising cathode materials for lithium‐ion batteries due to their large capacity and energy density, and their ability to use earth‐abundant elements. The excess Li in the rocksalt, needed to achieve good Li transport, reduces the theoretical transition metal redox capacity and introduces a labile oxygen state, both of which lead to increased oxygen oxidation and concomitant capacity loss with cycling. Herein, it is demonstrated that substituting the labile oxygen in Li‐rich cation‐disordered rocksalt materials with a vacancy is an effective strategy to inhibit oxygen oxidation. It is found that the oxygen vacancy in cation‐disordered lithium manganese oxide favors high Li coordination thereby reducing the concentration of unhybridized oxygen states, while increasing the theoretical Mn capacity. It is shown that in the vacancy‐containing compound, synthesized by ball milling, the Mn valence is lowered to less than +3, providing access to more than 300 mAh g −1 capacity from the Mn 2+ /Mn 4+ redox reservoir. The increased transition metal redox and decreased O oxidation are found to improve the capacity and voltage retention, indicating that oxygen vacancy creation to remove the most vulnerable oxygen ions and reduce transition metal valence provides a new opportunity for the design of high‐performance Li‐rich rocksalt cathodes. Abstract : Oxygen vacancy introduction in cation‐disordered Li5 Mn3 O6.5 (LMO‐V) cathode material significantly improves the capacity and voltage retention for lithium‐ion batteries relative to stoichiometric Li5 Mn3 O8 (LMO). The increased transition metal redox and decreased oxygen oxidation in LMO‐V are critical to the improved electrochemistry as the oxygen vacancies reduce the transition metal valence and remove the most vulnerable oxygen ions.